Mixed convection from a discrete heat source in enclosures with two adjacent moving walls and filled with micropolar nanofluids - Ahmed, S.E.; Mansour, M.A.; Hussein, A.K.; Sivasankaran, S. (Elsevier, 2016)
This paper examines numerically the thermal and flow field characteristics of the laminar steady mixed convection flow in a square lid-driven enclosure filled with water-based micropolar nanofluids by using the finite volume method. While a uniform heat source is located on a part of the bottom of the enclosure, both the right and left sidewalls are considered adiabatic together with the remaining parts of the bottom wall. The upper wall is maintained at a relatively low temperature. Both the upper and left sidewalls move at a uniform lid-driven velocity and four different cases of the moving lid ordinations are considered. The fluid inside the enclosure is a water based micropolar nanofluid containing different types of solid spherical nanoparticles: Cu, Ag, Al2O3, and TiO2. Based on the numerical results, the effects of the dominant parameters such as Richardson number, nanofluid type, length and location of the heat source, solid volume fractions, moving lid orientations and dimensionless viscosity are examined. Comparisons with previously numerical works are performed and good agreements between the results are observed. It is found that the average Nusselt number along the heat source decreases as the heat source length increases while it increases when the solid volume fraction increases. Also, the results of the present study indicate that both the local and the average Nusselt numbers along the heat source have the highest value for the fourth case (C4). Moreover, it is observed that both the Richardson number and moving lid ordinations have a significant effect on the flow and thermal fields in the enclosure.